1994
DOI: 10.1128/mcb.14.10.6531
|View full text |Cite
|
Sign up to set email alerts
|

v-src induction of the TIS10/PGS2 prostaglandin synthase gene is mediated by an ATF/CRE transcription response element.

Abstract: We recently reported the cloning of a mitogen-inducible prostaglandin synthase gene, TIS10/PGS2. In addition to growth factors and tumor promoters, the v-src oncogene induces TIS10/PGS2 expression in 3T3 cells. Deletion analysis, using luciferase reporters, identifies a region between -80 and -40 nucleotides 5' of the TIS10/PGS2 transcription start site that mediates pp6Wvsrc induction in 3T3 cells. This region contains the sequence CGTCACGTG, which includes overlapping ATF/CRE (CGTCA) and E-box (CACGTG) seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
181
1

Year Published

1995
1995
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(185 citation statements)
references
References 63 publications
(35 reference statements)
3
181
1
Order By: Relevance
“…Ras might activate a number of signal pathways, including the Raf-1/MEK/ERK pathway and the PI3K/ Akt/NF-B pathway (26,51,52). In murine fibroblasts, activation of the Ras/Raf-1/ERK1/2 signal pathway is required for COX-2 induction (50). In this study, we found that treatment of A549 cells with BK caused subsequent activation of Ras, Raf-1, and ERK, and that manumycin A, GW 5074, and PD 098059 all inhibited BK-induced ERK activation and COX-2 expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ras might activate a number of signal pathways, including the Raf-1/MEK/ERK pathway and the PI3K/ Akt/NF-B pathway (26,51,52). In murine fibroblasts, activation of the Ras/Raf-1/ERK1/2 signal pathway is required for COX-2 induction (50). In this study, we found that treatment of A549 cells with BK caused subsequent activation of Ras, Raf-1, and ERK, and that manumycin A, GW 5074, and PD 098059 all inhibited BK-induced ERK activation and COX-2 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Ras, an oncogenic protein, plays a critical role in inducing COX-2 expression (49,50). Ras might activate a number of signal pathways, including the Raf-1/MEK/ERK pathway and the PI3K/ Akt/NF-B pathway (26,51,52).…”
Section: Discussionmentioning
confidence: 99%
“…Since the e ects of D184-C/EBPb were transient in CEF and only observed in the ®rst hour following the activation of the thermolabile by pp60 v-src , this may explain why C/EBPb has not been identi®ed previously as a critical factor in the v-src dependent activation of this gene. Factors targeting the CRE are involved in the activation of Cox-2 by pp60 v-src in murine ®broblasts (Xie et al, 1994).…”
Section: C/ebpb Is Required For the Activation Of The Cef-4 Srumentioning
confidence: 99%
“…In brief, cDNA probes were synthesized in a 20-l reaction with 2 g of total RNA, 0.5 g of oligo(dT) [12][13][14][15][16][17][18] , 20 U of RNasin (Promega, Madison, WI), 4 l of 5ϫ RT Buffer, 0.5 mM dNTP, and 20 U of M-MLV reverse transcriptase enzyme (Life Technologies, Gaithersburg, MD).…”
Section: Real-time Pcr Analysis Of Tgf-␤ 1 Mrnamentioning
confidence: 99%
“…Preliminary evidence has been elaborated for possible involvements of the MAP-kinase and NF-B pathways (9 -11). In fact, the COX-2 gene promoter contains, apart from a classical TATA box, an E-box and a CRE-element, both representing binding sites for transcription factors such as NF-B (12)(13)(14)(15). A series of recent reports has provided evidence that the COX-2 promoter also contains binding sites for the nuclear factor of activated T cells (NFAT) (16 -19) and that activation of this factor stimulates COX-2 expression in several cell lines (16 -19).…”
mentioning
confidence: 99%